Pengaruh Lingkungan Kerja Terhadap Organizational Citizenship Behavior Yang Dimediasi Oleh Kepuasan Kerja Terhadap Karyawan Kantor PT. Sketsa Cipta Graha, Surabaya - Yuni Putri Dewantara; Damelina Basauli Tambunan (Peneliti.net, 2023)
The construction sector is a potential sector with many competitive competitors and companies with strong human resources are needed to win the competition. Organizational citizenship behavior plays a role in the company's success as a successful company requires human resources who works beyond the set expectations, without expecting any imbalance. Organizational citizenship behavior is an act of extra HR role in a company, regardless of all the industries the company is involved in. In forming a strong OCB, several factors are needed to influence it. This study will examine the effect of the work environment on organizational citizenship behavior which is mediated by job satisfaction of employees at PT. Sketsa Cipta Graha, Surabaya. The sample in this study amounted to 33 people. This study uses the Structural Equation Model - Partial Least Square Method using SMARTPLS 3.0 software. Based on the results of data analysis, it can be interpreted that the work environment has a significant effect on job satisfaction, job satisfaction and work environment have a significant effect on the behavior of organizational members, and job satisfaction mediates the significant influence of the work environment on the behavior of organizational members.